Rancang Bangun Aplikasi Sistem Gudang Berbasis Web Menggunakan Framework Laravel dengan Agile Development Studi Kasus pada PT XYZ - Robbani, Abdullah Azzam; Wiyono, Bambang Harie; Haromain, Imam (LPPM STT Terpadu Nurul Fikri, 2025)
The primary issue addressed in this research is the inability of the desktop-based warehouse management system used by PT XYZ to handle the complexity of modern logistics operations. This limitation leads to data inaccuracies, processing errors, lack of integration, limited accessibility, and inefficiencies that increase operational costs. Consequently, this study aims to develop a web-based warehouse management system using the Laravel framework and an Agile Development approach. The research adopts the Agile Development methodology, facilitating iterative development with continuous user feedback. The development process includes requirements analysis, system design, implementation, and testing. MariaDB is utilized as the database for inventory data storage, while Laravel handles backend logic. The interface is built with a combination of Blade Template and JavaScript, ensuring an intuitive user experience. As a result, developing a web-based warehouse system using Laravel and Agile Development was successfully carried out with features that support real-time warehouse operations, such as stock monitoring, recording incoming and outgoing goods, and automating invoicing. This system improves operational efficiency and reduces inventory recording errors by automating processes previously done manually.